Fundamentals of Object-Oriented Languages, Systems, and Methods
During the last decades there has been progress within the object-oriented community in agreeing on what object- orientedness means. The role of object identity, specialization, inheritance, and dynamic binding have been examined. However, a careful look at articles written by people with a theory, programming language, database, and software engineering background shows that the semantical understanding of the same features still differs considerably. A well-known example is the feature of inheritance, which has quite a different meaning for persons from the database comunity with a semantic data model background and persons form the programming language community with a compiling technique background This observation also applies to the literaute on object-oriented software development methods. Here, object -oriented analysis and design methods are often heavily influenced by semantic data modelling consepts- An implemantion of an object-orinted design by an objeckt-oriented progamming language usually causes more difficulties than expected although the "same" object-oriente paradigm is used...

Graph Gramars and Their Application to Computer Science, 5th International Workshop (1994), Selected Papers

Berücksichtigung von Datenschutzaspekten in einem bevölkerungsbezogenen Krebsregister - Thoben, Wilfried; Appelrath, Hans-Jürgen; Rettig, Jens; Sauer, Stefan (Proceedings of the conference on Medizin und Information, Biometrie und Epidemiologie (GMDS 1994), Dresden (Germany))
Die Pilotphase 1993/ 94 zum Aufbau eines Niedersächsischen Krebsregister untersucht das im Entwurf des Bundeskrebsregistergesetzes vorgesehen Modell für ein bevölkerungsbezogenes Krebsregister. Darin werden die Krebsmeldungen in einer Vertrauensstelle erfaßt und die personenidentifizierenden Daten vor der Übermittlung an die Registerstelle anonymisiert, wo sie dann zu einem bevölkerungsbezogenen Krebsregister verdichtet und epidemiologischer Forschung zur Verfügung gestellt werden ([1], [2], [3]). Dieses sogenannte „Michaelis“-Modell erlaubt eine bevölkerungsbezogene Registrierung von Krebsfällen unter Berücksichtigung datenschutzrechtlicher Aspekte („Informationelles Selbstbestimmungsrecht“) der einzelnen Betroffenen. In vier Teilprojekten werden dabei in der Modellregion Weser-Ems die Integration krebsregistrierender Einrichtungen, die Chiffrierung/ Dechiffrierung von Krebsmeldungen, der Abgleich anonymisierter Meldungen in der Registerstelle und die Entwicklung eines epidemiologischen Informationssystem betrachtet ([4], [5]).

Structural and Behavioural Views on OMT-Classes - Ebert, Jürgen; Engels, Gregor (Proceedings of the International Symposium on Object-Oriented Methodologies and Systems (ISOOMS 1994), Palermo (Italy))
Object-oriented specification languages provide means to specify the static structure, as well as the allowed dynamic behaviour of objects. Here, the dynamic behaviour is usually described by giving the methods and a state transition diagram which defines the allowed sequences of methods on objects of a certain class. Specialized classes are defined using the inheritance relationship. In order to enable reusability while guaranteeing type substitutability, subclass specifications have to be compatible with respect to static and dynamic aspects with their corresponding superclass specifications. Classes have to provide a large shopping list of operations to satisfy the needs of all possible users. The interests of specific users are often restricted to a subset of operations and thus to a restricted behaviour. This paper describes a formalization of class descriptions given by attributes, operations, as well as state transition diagrams. It defines compatibility between sub- and superclasses and introduces the notion of views in the sense of hiding parts of a class description. It turns out that a view has the same properties as a (virtual) superclass.

Object-Oriented System Development: Will the New Approach Solve Old Problems? - Engels, Gregor; Kappel, Gerti (Proceedings of the IFIP 13th World Computer Congress on Information Processing, Hamburg (Germany))
Object-oriented system development is wideley recognized as improving productivity and reducing system maintenance costs. However, existing approaches have not sufficiently addressed the following three questions which are equally important to users and researchers. Firstly, what are the benefits of object-oriented system development compared to traditional approaches? Secondly, what are the essential features of an objectoriented life cycle model to fulfill the benefits of object-oriented development? And thirdly, what are the pitfalls of object-oriented development and how to cope with them? The paper investigates answers to all three questions in concert.

Towards a Module Concept for Graph Transformation Systems: The Software Engineering Perspective - Engels, Gregor; Ehrig, Hartmut (Proceedings Colloquium on Graph Transformation and its Application in Computer Science)

Optical Modelling, Simulation and Improvement of PV Module Encapsulation - Krauter, Stefan; Hanitsch, Rolf; Campbell, P.; Wenham, S.R. (Proceedings of the 12th European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 11.–15. April 1994, Band 2, S. 1198–1201)

Simulation Tool for Prediction and Optimization of Output Power Considering Thermal and Optical Parameters of PV Module Encapsulation - Strauss, Philipp; Onneken, K.; Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 12th European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 11.–15. April 1994, Band 2, S. 1194–1197.)

Einfluß optischer und thermischer Parameter auf den Tageswirkungsgrad von photovoltaischen Modulen - Krauter, Stefan; Hanitsch, Rolf (Neuntes Internationales Sonnenforum, Berlin (Deutschland), 28. Juni – 1. Juli 1994, S. 495–502)

Simulation of Thermal and Optical Performance of PV Modules - Krauter, Stefan; Hanitsch, Rolf; Wenham, S. R. (Proceedings of the 3rd World Renewable Energy Congress, Reading (UK), 11.–16. September 1994)

Actual Optical and Thermal Performance of PV-Modules - Krauter, Stefan (Proceedings of the 1st World Conference on Photovoltaic Energy Conversion (Joint Congress of IEEE/PVSEC/EUPVSEC), Waikoloa, Hawaii (USA), 5.–9. Dezember 1994, S. 734–737.)

Observable or Invocable Behaviour - You Have to Choose - Ebert, Jürgen; Engels, Gregor

Syntax and Semantics of Hybrid Database Languages - Andries, Marc; Engels, Gregor (Proceedings of the International Workshop on Graph Transformations in Computer Science (1993), Dagstuhl (Germany))
We present the hybrid query language HQL/EER for an Extended Entity-Relationship model. As its main characteristic, this language allows a user to freely mix graphical and textual formulation of a query. We show how syntax and semantics of this hybrid language are formally defined by means of a slightly extended version of PROGRES, a specification formalism based on programmed and attributed graph rewriting systems.

Specification of coordinated behaviour by SOCCA - Engels, Gregor; Groenewegen, Luuk (Proceedings of the Third European Workshop on Software Process Technology (EWSPT 1994), Villard de Lans (France))

Visual Specification of Complex Database Actions - Engels, Gregor; Löhr, Perdita (Proceedings of the 2nd International East/West Database Workshop, Klagenfurt (Germany))
The paper presents an approach to specify in an integrated way by visual, diagrammatic languages the structural and behavioural aspects of database applications. Hereby, well-known extended Entity-Relationship diagrams are employed to specify the structural aspects. The behavioural aspects of a database application are specified by using ViAL (Visual Action Language). ViAL specifications are a special kind of data (or better object) flow diagrams, where so-called elementary actions are used as basic building blocks. These elementary actions are automatically derived from a given EER diagram. They guarantee that after finishing their execution all inherent integrity constraints are fulfilled. The paper explains the features of the language ViAL and gives some illustrating examples.

Visuelles Spezifizieren von komplexen Aktionen auf Datenbankstrukturen - Löhr-Richter, Perdita; Engels, Gregor (GI-Datenbank Rundbrief)

Design Representation - Ebert, Jürgen; Engels, Gregor (Encyclopedia of Software Engineering)
This article gives an overview on how to represent the outcome of the software design phase in design documents. The descriptive aspects of the design description languages are stressed. The focus is on sequential systems and the description is arranged according to the main paradigms that are used in indentifying software components. Following a general discussion on how to represent software architectures of large systems, each design paradigm is discussend separately with its basic concepts, its historical background and its main variants. Some multiparadigmatic approaches are discussed, as well which integrate several of the aspects introduced before.

SOCCA: Specifications of Coordinated and Cooperative Activities - Engels, Gregor; Groenewegen, Luuk (Software Process Modelling and Technology)

Windatlas für das PESAG-Versorgungsgebiet - Bendfeld, Jörg; Ernst, Achim; Ortjohann, Egon

Flächendeckende Windpotentialbestimmung in einer Binnenlandregion mit ausgeprägter Orographie - Bendfeld, Jörg; Ernst, Achim; Ortjohann, Egon; Langrock, Beate; Scholz, Norbert (Renergie 94 - Windenergienutzung im Binnenland, Solarenergienutzung in Deutschland)